Hubungan Tingkat Pengetahuan Ibu dengan Kejadian Kekambuhan Asma Pada Anak Di Puskesmas Sibela Kota Surakarta - Nurtiyastuti, Novia Ayu; , Siti Arifah, S.Kp., M.Kes (2016)
Asthma in a chronic disease that most often found on childrens in the develop country, the incidence of asthma is almost 6 million. Survei health national from centers for disease control and prevention got the prevalence of asthma lifetime was 12,5% and the prevalence of asthma at that time was 8,5% on the less than 18 years children. The reccurance of asthma begins in childhood and develops before 5 years old. Asthma is more severe in children because they are more susceptible to infections and airway size cooler and smaller thereby increasing airway resistance. Increased prevalence of asthma is suspected due to undiagnosed, poor air quality and the changing lifestyle of the people, lack of education of patients is estimated to be the cause of increased asthma sufferers. The purpose of this study is to determine the relationship with the mother's level of knowledge of the incidence in recurrence of asthma in children in Sibela Clinic Surakarta. The type of this research is descriptive correlation with cross sectional study that was conducted in September-December 2016 in Sibela Clinic Surakarta. These samples were taken by accidental sampling with a sample size of 39 people. The independent variable is the incidence of recurrence of asthma, while the dependent variable is the level of mothers' knowledge of asthma relapse. The research instrument was a questionnaire. Data were analyzed by Spearman Rho (ɑ ≤ 0,05). In this study showed that there is a relationship between the mother's level of knowledge in incidence of recurrence of asthma in children in Sibela Clinic Surakarta (p = 0.000). From the data above, the researcher can conclude that the lower the level of knowledge of the mother, the more often children experience asthma relapse. For the further researcher is expected to develop a better research, so they can answer the factors that influence about the reccurence of asthma on children and the hencmark for their achievment. Keywords: Mother Knowledge, Recurrence of Asthma, Asthma. Compiled from 41 libraries in 2005-2016